The Soul Revolution: an Integrative Study on Creating a New Human in the Islamic Civilization (Journal of Islamic Thought and Philosophy, 2026)
This article aims to identify the reason behind the greatest revolution in human history. The revolution has astonished thinkers, both ancient and modern, due to its profound impact and lasting effects. This research used a qualitative, descriptive, and library-based approach to examine what has been written about that revolution, whether from the Qur'an, the Sunnah, or the works of scholars and thinkers. The findings of this research showed that the starting point of that revolution was the soul as the essence of humankind. Tawhīd, as the essence of Islam, has brought them out of the greatest complication of their souls. The Prophet Muhammad had educated them successfully by purifying their souls and practicing the highest moral standards. Through this new formation of soul, character, and behavior, they were transformed to be the best creatures God had ever produced for all humankind.